Chicory root flour – A functional food with potential multiple health benefits evaluated in a mice model. (November 2020) - Pouille, Céline L.; Jegou, Doriane; Dugardin, Camille; Cudennec, Benoit; Ravallec, Rozenn; Hance, Philippe; Rambaud, Caroline; Hilbert, Jean-Louis; Lucau-Danila, Anca
Graphical abstract: Highlights: Chicory roots impact genes expression, hormones release, gut microbiota composition. Chicory roots provide cancer protection, antimicrobial effect and metabolic regulation. Chicory effects are more pronounced in male mice than in female mice. Chicory root flour triggers different health effects than inulin alone. Abstract: Industrial chicory roots ( Cichorium intybus var. sativum ) have been the subject of many different studies investigating their supposed nutritional and medicinal benefits. Although an impressive number of clinical evidences has supported the health effects of this plant, the molecular mechanisms remain poorly understood. In this work, we looked at chicory flour that is proposed as an ingredient for pastries and a water extract of chicory root flour was tested. We experimented on the murine model and highlighted new mechanisms by which the chicory roots brings health benefits. For this purpose, a nutrigenomic analysis was associated with a metabolic hormone dosage and a metagenomic analysis. New potential mechanisms by which the chicory acts on cancer prevention on antibacterial and antiviral defense, on hypoglycemic and hypolipidemic effect as well as on the antioxidant effect were identified. Also, the prebiotic effect of the chicory root flour was discussed by comparison with inulin. In general, almost all effects were found to be more pronounced in male mice than in female mice.